The Effectiveness of Learning Basic Passing Techniques Under Volleyball Games for Class VIII Students of SMP Negeri 02 Martapura East OKU District - Suyatno, Suyatno; Wardiah, Dessy; Hermansah, Bambang (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this research is that volleyball is a type of game sport that is favored by the community and has been determined as a sport that is competed in various events at regional, national and international levels. The fact that based on observations shows that the ability to pass down in grade VIII students of SMP Negeri 02 Martapura, East OKU Regency is still very low on average. The purpose of this study was to determine the improvement of the learning ability of lower passing motion in students. The population of this study was all grade VIII students of SMP Negeri 02 Martapura and were taken to be sampled as many as 30 students. The research method used is follow-up assessment research, namely through exercise or treatment, in each action is in every cycle that has been determined. Tests are carried out at the beginning of the study and the end of the study. The data obtained through tests and observations are then analyzed descriptively using percentage techniques. The result is; 1. Initial test result success 0%, 2. First cycle test results success 6.67% (2 people), 3. Cycle II test results success 23.33% (7 people), 4. The results of the third cycle test were 63.33% successful (19 people). Based on the results of the research above, it can be concluded that onion passing learning can improve the ability to pass down in grade VIII students of SMP Negeri 02 Martapura, East OKU Regency.